A Model for the Estimation of Surface Tension of Pure Hydrocarbon Liquids - Aleem, W. (Taylor and Francis Inc., 2015)
Surface tension is an important property and its accurate prediction is required in most chemical engineering calculations. An equation for the surface tension of liquid hydrocarbons as a function of temperature is developed considering intermolecular attractions in liquid phase are reflected by its enthalpy. The model equation is validated with National Institute of Standards and Technology data on liquid hydrocarbon alkanes (C1 to C10 and C12) accounting for molecular shape through sphericity factor. The molecular sphericity factor correlated well with molecular weight of the hydrocarbons. The accuracy of the proposed model equation is compared with the two empirical equations, and results showed that the proposed model equation predicts the surface tension of pure hydrocarbon liquids more accurately. Copyright Â© 2015 Taylor & Francis Group, LLC.